Audit Judgment Performance: The Effect of Performance Incentives, Obedience Pressures and Ethical Perceptions - Nugrahanti, Trinandari P.; Jahja, Adi Susilo (Journal of Environmental Accounting and Management, 2026)
This study aims to analyze the influence of performance incentives, obedience pressures and ethical perceptions to audit judgment in auditors’ professional activities. Data collection was conducted by distributing questionnaires to auditors from public accounting firms in Indonesia. The result showed that the performance incentives increase the performance of audit judgment. The obedience pressures of auditors profoundly influenced the performance of audit judgment performance of auditors whereas the ethical perception has no effect on audit judgment. This study suggests that auditors should pay attention to auditing standards and professional codes of ethics, encourage auditors to be able to overcome the pressures and behave by the professional ethical standards. Therefore audit firms should provide performance incentives. Finally, the study shows that the Institute of Public Accountants Indonesia (IAPI) is expected to always conduct continuous professional education (PPL) for the audit profession in order to implement the audit standards and professional code of ethics.